Carl Nielsen, Ebbe Hamerik and the First Symphony - Krabbe, Niels (Carl Nielsen Studies, 2003)
In 1928, the Danish composer and conductor Ebbe Hamerik gave a performance of Nielsen’s First Symphony, containing scattered changes in the original instrumentation and a rather drastic change of a certain passage in the fourth movement, which is clearly to be seen from the score and the parts used by Hamerik for his performance. In the standard literature on Carl Nielsen it is related how Nielsen heard this performance, and how towards Emil Telmányi, his son-in-law, he showed his strong disapproval of Hamrik’s intervention – to such a degree that he insisted on performing the work himself a fortnight later in order to show how he, the composer, really wanted the work. Through a study of a number of sources, illuminating these matters it is shown that Nielsen, very far from disapproving Hamerik’s version found it highly convincing and apparently used Hamerik’s parts and score for his own performance two weeks later. It even appears that Nielsen himself actually composed the changed passage in the fourth movement and probably sent it to Hamerik to be orchestrated.